Sex-specific Effects of Spironolactone on Blood Pressure in Gonadectomized Male and Female Wistar Rats - Michaelis, M.; Hofmann, P. J.; Götz, F.; Bartel, C.; Kienitz, T.; Quinkler, M. (Hormone and Metabolic Research, 2012)
A low-salt diet is known to decrease and salt excess to increase blood pressure in humans and rodents. Sex steroids seem to play a role in salt dependent hypertension. However, little is known about sex differences in mineralocorticoid receptor blockade between male and female rats. The objective of the work was at first to investigate the effects of a low-salt vs. a high-salt diet on blood pressure without the influence of gonadal steroids in male and female rats. Second, to determine the sex-specific effects of mineralocorticoid receptor blockade by spironolactone in high-salt and low-salt fed gonadectomized male and female animals. Normotensive male and female Wistar rats were gonadectomized and put on a low (NaCl<0.03%) or high (NaCl=4%) salt diet. On each diet animals received spironolactone or placebo. Blood pressure was measured by tail-cuff-method; 24-h urine samples were collected in metabolic cages and blood was collected for hormonal measurements. High-salt diet significantly increased systolic blood pressure in both sexes. This effect could be blocked effectively by spironolactone only in male rats. Spironolactone treatment significantly increased aldosterone levels in males and females independent of the sodium content of the diet. High sodium diet significantly increased relative kidney weight, which was not altered by spironolactone treatment. Independently of gonadal steroids a high-salt diet increased blood pressure in gonadectomized male and female rats. Spironolactone lowered blood pressure only in male not in female rats on a high-salt diet clearly indicating sex-specific effects of the mineralocorticoid antagonist spironolactone.
Keywords: high and low salt diet; aldosterone; spironolactone; sex difference; hypertension; mineralocorticoid receptor antagonist